Relación entre los usos populares de la granadilla (Passiflora ligularis juss) y su composición fitoquímica (2014)
ABSTRACT: This article reports the common uses of the Passiflora ligularis juss among the farm workers in the department of Huila and the preliminary results of its phytochemical composition. In the first phase of this investigation, an ethnobotany survey distributed among 42 families was consulted to create an inventory of the agricultural uses of the different parts of the plant. This information served as a starting point to select the basic qualitative analysis which allows the identification of biological activity of this species such as the phytochemical analysis, the bromatological analysis, and the mineral analysis. Twenty six common uses were discovered especially for medical and nutritional purposes. Some medicinal uses may be related to the qualitative presence of compositions found in the phytochemical analysis. The use of the grenade’s outer shell for animal nutrition was found to be justified based on the calories and fiber. This study highlights the finding that the pulp of the fruit is a source of magnesium for children younger than a year. Significant differences were found in the composition of the grenade’s pulp of three different areas due to agroecological conditions and the mineral nutrition that the plants receive.